Systemic antibiotics increase microbiota pathogenicity and oral bone loss - Xulei Yuan; Fuyuan Zhou; He Wang; Xinxin Xu; Shihan Xu; Chuangwei Zhang; Yanan Zhang; Miao Lu; Yang Zhang; Mengjiao Zhou; Han Li; Ximu Zhang; et al. (Nature Publishing Group, 2023)
Abstract Periodontitis is the most widespread oral disease and is closely related to the oral microbiota. The oral microbiota is adversely affected by some pharmacologic treatments. Systemic antibiotics are widely used for infectious diseases but can lead to gut dysbiosis, causing negative effects on the human body. Whether systemic antibiotic-induced gut dysbiosis can affect the oral microbiota or even periodontitis has not yet been addressed. In this research, mice were exposed to drinking water containing a cocktail of four antibiotics to explore how systemic antibiotics affect microbiota pathogenicity and oral bone loss. The results demonstrated, for the first time, that gut dysbiosis caused by long-term use of antibiotics can disturb the oral microbiota and aggravate periodontitis. Moreover, the expression of cytokines related to Th17 was increased while transcription factors and cytokines related to Treg were decreased in the periodontal tissue. Fecal microbiota transplantation with normal mice feces restored the gut microbiota and barrier, decreased the pathogenicity of the oral microbiota, reversed the Th17/Treg imbalance in periodontal tissue, and alleviated alveolar bone loss. This study highlights the potential adverse effects of long-term systemic antibiotics-induced gut dysbiosis on the oral microbiota and periodontitis. A Th17/Treg imbalance might be related to this relationship. Importantly, these results reveal that the periodontal condition of patients should be assessed regularly when using systemic antibiotics in clinical practice.